Itens lexicais em : "Relação das povoações de Cuiabá e Mato Grosso de seus princípios até os presentes tempos", de José Barbosa de Sá - 1879 - Maggi, Michele Barth (2018)
The present dissertation is constituted by the presentation of a copy of the original index of frequency and occurrences of lexical items, a codex named "Relação das Povoações de Cuiabá e Mato Grosso de seus Princípios até os Presentes Tempos, dated in 1879, belonging to the Brazil National Digital Library - BNDigital, in facsimilar form. The manuscript is composed of ninety-five (95) folios, recto, front page and back in which the socio-historical, political, administrative, economic, religious and juridical facts of the beginning of the settlement of Vila Real do Senhor Bom Jesus de Cuiabá are narrated, transformed in the city of Cuiabá. For the elaboration of the index of frequency and occurrences, nouns, adjectives and verbs are inventoried in order to obtain the vocabulary of the codex. A textual statistical program named Lexicon 3 is used to identify the occurrences of the lexical items, and a software specifically designed and produced to identify the frequency and location of these items is applied. This index enables the realization of the considerations regarding the result obtained, represented by means of graphs and notes relating the lexical items to the socio-historical facts narrated in the codex. It has a philological character, because it shows a codex written from 1719 to 1775, and then copied in the year of 1879, that is, more than one century carrying records of the relevant facts of the history of the formation of the first settlements of Cuiabá. It testifies the Portuguese language at the time, the semidiplomatic edition being chosen for the transcription with the purpose that the reader has a greater legitimacy of the information. As a theoretical basis for the organization of the Index, Ferreira et al. (2005) and Borba (2003) are cited, for philological studies and fac-simile and semidiplomatic editions Cambraia (2003), Spina (1977) Castro (1992) are cited and for considerations about the Index Biderman (1984, 1999, 2001) is cited. This codex contributes to the transmission and preservation of the facts that occurred in a remote Cuiabá, by bringing the cultural richness of a significant time for the colonization of this land and for future linguistic studies on the lexicon of the Portuguese Language.